Objective and subjective hyposalivation after treatment for head and neck cancer: Long‐term outcomes. (16th October 2018) - Likhterov, Ilya; Ru, Meng; Ganz, Cindy; Urken, Mark L.; Chai, Raymond; Okay, Devin; Liu, Jerry; Stewart, Robert; Culliney, Bruce; Palacios, Daisy; Lazarus, Cathy L.
Abstract : Objectives/Hypothesis: This study examined saliva weight over time and its association with diet and patient‐rated swallowing, dry mouth, sticky saliva, and dysgeusia quality of life in head and neck cancer (HNCA) patients treated with surgery plus adjuvant chemoradiotherapy (CRT), or primary CRT. Study Design: Prospective cohort study in an outpatient HNCA center setting. Methods: Patients were seen pretreatment, and 1, 3, 6, 12, 24, and 36 + months post‐treatment. All had newly diagnosed oral, oropharynx, nasopharynx, larynx/hypopharynx cancer from 2010 to 2016 and were to undergo surgery + CRT or primary CRT. Stimulated saliva weight was assessed with the Saxon test. Diet, eating, dry mouth, and dysgeusia quality of life were assessed and correlated with saliva weight, treatment modality, and tumor site. Results: Saliva weight decreased the most within the first 3 months across treatment groups, except for the surgery + CRT group, which continued to decline. Similar trends were seen by tumor site. Performance Status Scale (PSS) Normalcy of Diet and all quality‐of‐life scores declined following treatment. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck‐35 (EORTC QLQ‐H&N35); Eating Assessment Tool (EAT‐10); M. D. Anderson Dysphagia Inventory (MDADI) Composite, Global, and subdomain scores; and PSS Diet were significantly correlated with saliva weight. Conclusions: Saliva weight worsened post‐treatment across groups and tumor site, with improvement by 36 + months. Saliva weight correlated with diet, eating quality of life and perception of dysgeusia across time points. Despite dose‐sparing intensity‐modulated radiation therapy, newer technologies are needed to preserve saliva production and maintain higher quality of life. Level of Evidence: 2b Laryngoscope, 128:2732–2739, 2018